Provolone del Monaco PDO cheese: Lactic microflora, biogenic amines and volatilome characterization - Scarano, Luigi; Peruzy, Maria Francesca; Fallico, Vincenzo; Blaiotta, Giuseppe; Aponte, Maria; Anastasio, Aniello; Murru, Nicoletta (Food research international, 2024)
[Display omitted] •A Provolone del Monaco production process was monitored starting from the milk.•371 LAB cultures were subject to PFGE characterization followed by identification.•4 cheeses produced and ripened under the same conditions were analysed at 623 days.•Only three of the four cheeses shared a similar microbiome by HTS.•One cheese sample out of 4 showed high BAs content and a different VOCs profile. One commercial production run of Provolone del Monaco − a long-ripened pasta filata cheese − was followed up to the end of ripening for a total of 20 samples. 371 LAB isolates were subject to genetic characterization followed by 16S rRNA gene sequencing. The dominant species were Lacticaseibacillus casei/paracasei (19.4 %), Streptococcus macedonicus (19.1 %) and Enterococcus faecalis (13.2 %). Strains were screened for features of technological interest or safety relevance. Tyramine-producing cultures were quite common, above all within enterococci. By MALDI TOF Mass Spectrometry, one Lactococcus lactis and one Enterococcus faecium strain proved to be bacteriocin producers. Four further cheese wheels from the same production run at 623 days of ripening were evaluated for volatile organic compounds, biogenic amines, and bacterial community by metagenomic sequencing. Three individual wheel samples shared a rather similar microbiome with Lactobacillus delbrueckii and Streptococcus thermophilus as the most represented species, while the fourth wheel appeared wholly different being dominated by Lentilactobacillus buchneri and St. infantarius. Additionally, this sample had the greatest content of biogenic amines and a different VOCs composition. Given the variance seen among cheese wheels processed and ripened under the same conditions, the search for adjunct cultures in the production of this cheese seems to be of utmost importance.